A rare case of Gingival Myeloid sarcoma in a child (Journal of Pathology of Nepal, 2017)
Myeloid sarcoma is a rare tumour composed of immature myeloid cells. Its occurrence in childhood is rare. Only a few cases of intraoral myeloid sarcoma have been reported in literature. We present a case of myeloid sarcoma with simultaneous involvement of intraoral soft tissues and lymph node. Here, importance is given to suspect this frequently misdiagnosed disease.